Effective grid interfaced renewable sources with power quality improvement using dynamic active power filter. (November 2016) - Kasa, Sudheer; Ramanathan, Prabhu; Ramasamy, Sudha; Kothari, D.P.
Highlights: Model describes effective utilization of renewable sources without additional components. Model reduces harmonics in source, load & wind currents. UPF is brought at source end. Continuity of power supply to load is maintained. Source serves only real power to the load. DAPF uses solar unit for DC link voltage conditioning and active power injecting. Abstract: The present modern power system is getting more complex and dynamic day by day. These Dynamic changes can be effectively handled by integrating renewable sources to the grid. The optimal usage of renewable sources will improve the overall performance of the electrical utility. Renewable energy sources and non-linear loads connected to grid have adverse effects on the power quality of the system. This paper presents I cosine ANFIS control based Dynamic Active Power Filter (DAPF) to improve the power quality of the grid at source side with effective integration of renewable sources. The model presents optimal usage of renewable sources and avoids the usage of battery by replacing with solar energy unit (SEU). DAPF fed by SEU and wind unit serves power to the load during power fluctuations from grid side. The performance of proposed model with I cosine ANFIS controller based DAPF is validated using MATLAB/SIMULINK.